Development of a Simple Checklist Model for Family Centered Care in Non-pharmacological Pain Management in Post-operative Wounds in Children - Puspita, Mefrie; Dasuki, Dasuki; Hetrini, Hetrini; Berliana, R.A. Berliana (Universitas Muhammadiyah Tangerang, 2025)
Background: Post-operative wound pain felt by children can be minimized with non-pharmacological pain management interventions. Parental involvement is very important in providing nursing care by pediatric nurses using the Family Centered Care (FCC) approach. Non-pharmacological pain management interventions that can be carried out by families include giving hugs, support, carrying, using distraction techniques and playing with the child. Objective: There is no monitoring sheet for the implementation of Family Centered Care in hospitals, especially in children's care rooms, carried out by pediatric nurses. For this reason, this research will be carried out with the aim of developing a simple checklist model for implementing Family Centered Care in carrying out non-pharmacological pain management in post-operative wounds in children. The research will be carried out in the pediatric care room of a hospital in Jambi Province. Method: The research method used is quantitative research with a descriptive design to determine the relevant level of instrument use. The sampling technique uses total sampling. The total sample was 37 pediatric nurses. Results: The results of the instrument field test were declared valid and reliable with r-count > r-table, namely 0.446-0.795 > 0.334. The instrument was declared reliable with Cronbach's alpha > r-table, namely 0.927 > 0.334. Conclusion: The 25 items in the instrument can be applied in the pediatric room for non-pharmacological management of post-operative wound pain. Keywords: Checklist model; Family Centered Care; Pain; Post-operative wounds